PENGARUH KONFLIK DAN STRES KERJA TERHADAP KINERJA KARYAWAN DI FAVE HOTEL KARTIKA PLAZA (Studi Pada Fave Hotel Kartika Plaza) - I Putu Yoga Negara; Ni Luh Sili Antari (Journal Research of Management, 2020)
Human resource management is part of organizational management that focuses on the elements of human resources. The task of Human Resource Management (HRM) is to manage the human element well in order to obtain a workforce that is satisfied with their work. The problem raised in this study is whether the conflict (X1) affects the performance of employees (Y) at the Fave Hotel Kartika Plaza, and whether work stress (X2) affects the performance of employees (Y) in Kartika Plaza Hotel Fave and how much influence is the Conflict (X1) and work stress (X2) on Employee Performance (Y) in Fave Hotel Kartika Plaza. The population in this study amounted to 75 people. This study uses the entire population as a sample. Data analysis techniques used are data quality test, classic assumption test, multiple linear regression analysis, t-test analysis and analysis of determination. The results of the analysis show the regression model Y = 10,157 - 0,446X1 - 0,035X2. The conclusion obtained is the conflict (X1) partially has a negative and significant effect on employee performance (Y) in the Fave Hotel Kartika Plaza shown by the regression coefficient b1 X1 which is negative, work stress (X2) partially has a negative and significant effect on the performance of employees (Y) in Fave Hotel Kartika Plaza as indicated by thecoefficient b2 X2 negative, and the magnitude of the effect of work conflict (X1) and work stress (X2) on employee performance (Y) of 52.8% and the remaining 47.2% is influenced by other variables such as motivation, work environment and work discipline that are not discussed in this study.